Factors Affecting the Implementation of Nursing Round - Moi, Maria Florentina; Nursalam, Nursalam; Asmoro, Candra Panji (Universitas Airlangga, 2019)
Introduction: Introduction: Nursing rounds aimed to solve patient nursing problems performed by nurses and patients to discuss and implement of nursing care. The implementation of the nursing round can be influenced by knowledge, attitudes, subjective norms, and intentions. The purpose of this study was to determine the factors that influence the nursing round in the Inpatient Room of Bajawa Hospital. Method: The design of this study was cross-sectional. The total population were 108 and obtainned 98 respondents by total sampling. Independent variables were knowledge, attitudes, subjective norms, and intentions. The dependent variable was the implementation of the nursing round. The instrument used a questionnaire. Data was analyzed by Spearmen's Rho.Result: Dominant factor on implementation of nursing round was intention (p=0.007). There was a relationship between knowledge and attitude (p=0.000), knowledge with subjective norms (p=0.000), attitudes with intentions (p=0.004), subjective norms with intentions (p=0.002), intention with nursing rounds (p=0.030).Conclussion: The implementation of the nursing round will run well with good knowledge, positive attitude, good subjective norms, and good intentions from the nurse to carry out the nursing round. So that training in nursing rounds is needed and the implementation of nursing rounds should be regular and continuous.